Genetic variations and clinical implications of B-thalassemia in Iraqi population - Ayman Ziadoon Jawad; Meryam Chelly; Salah Hashim AL-Zuhairy; Hanen Bouaziz (PLoS ONE, 2026)
β-thalassemia is a prevalent genetic disorder in Iraq, leading to significant health issues due to reduced hemoglobin production. The DNA sequencing technique was used to explore genetic variations and their clinical implications. Our findings have the potential to inform diagnosis, guide targeted therapeutic approaches, and enhance genetic counseling to reduce long-term morbidity in affected individuals. Peripheral blood samples were collected from 100 patients for analysis. Quantitative measurements included complete blood count (CBC), ferritin, parathyroid hormone (PTH), lactate dehydrogenase (LDH), 25‑hydroxyvitamin D, phosphorus, calcium, and bone mineral density (BMD) measured by dual-energy X-ray absorptiometry (DXA). We detected 18 β-globin mutations in β-thalassemia patients by direct Sanger sequencing, of which two were novel (HBB:c.315 + l08A>G and HBB:c.316-151A > G). Additionally, four mutations (IVS-II-1G > A, IVS-II-5G > C, IVS-I-110G > A, and HBB:c.440A > C) have been previously reported as pathogenic. This research pinpointed four β-globin gene pathogenic mutations as having significant associations with clinical parameters. Hematological parameters (HGB, WBC, RBC indices, RBC count) and biochemical/metabolic markers (phosphorus, PTH, LDH, ferritin, vitamin D3, calcium, ALP) exhibited strong statistical differences ( p < 0.001–0.020) across mutation groups. Bone health markers (BMC, BMD) and red blood cell indices (MCH, MCHC, MCV, MPV) also showed significant variation ( p < 0.001–0.002). In contrast, platelet count (PLT) did not differ significantly ( p = 0.331). These findings highlight mutation specific impacts on hematological, metabolic, and skeletal systems in the studied population.